UPAYA HUKUM DALAM PENYELESAIAN SENGKETA HAK KEKAYAAN INTELEKTUAL (Studi Kasus Putusan Nomor 41 PK/Pdt.Sus-HKI/2021) - Saraswati, Mardiana; Fuad, Fokky; Machmud, Aris (Lex Jurnalica, 2024)
AbstractThe law protects individuals and legal entities in certain cases to challenge a judge's decision as a forum for parties who are dissatisfied with a judge's decision that is deemed not to fulfill a sense of justice. In civil cases, legal remedies include ordinary legal remedies and extraordinary legal remedies. Extraordinary legal remedies are made for decisions that have permanent legal force (incracht van gewijsde), including a judicial review (request civil). This study aims to answer the formulation of the problem by analyzing the Copyright Law as a positive law in providing intellectual property protection for songwriters in Indonesia, and how other legal remedies can be made against decisions in the first instance court that have permanent legal force in copyright infringement cases. This study analyzes the copyright infringement of the song